Inovasi Kue Lumpur Berbahan Dasar Pisang Ambon Dan Tepung Kacang Hijau - Felia Rana Amanda; Any Sutiadiningsih; Asrul Bahar; Lilis Sulandari (Journal of Creative Student Research, 2023)
This research is about mud cakes were made by proportioning the main ingredients, namely banana ambon puree and mung bean flour. This study aims to determine: 1) sensory quality of mud cake made from banana ambon and mung bean flour, 2) nutritional content of mud cake made from banana ambon and mung bean flour, 3) cost of raw materials needed to make mud cake made from banana ambon and mung bean flour. This type of research is an experimental study of making mud cake made from ambon banana and mung bean flour with 3 treatments with proportions of 70%: 30%, 80%: 20%, 90%: 10%. Data collection was done by observation method through sensory test. The product was rated by 40 panelists. Data were analyzed using one way anova test, followed by Duncan's test. The results showed: 1) the best product based on the results of the analysis with sensory quality is obtained in mud cake with the treatment of 90% ambon banana puree and 10% mung bean flour, 2) the results of the best mud cake product criteria test show that it has a water content of 38.26%, fat 4.98%, protein 6.24%, carbohydrates 48.50%, and ash 1.24%, 3) the cost of raw materials needed in making mud cake made from ambon banana and mung bean flour is Rp 23,646.